Post-mastectomy breast reconstruction... A new life - Müller, Coralee (Operating Room Nurses Association of Canada Journal, 1987)
Mastectomy is the surgery most feared by women. It is the surgery many women never thought possible. One out of every 11 women in Canada will be faced with the issue of breast cancer and the excision of the breast, or a mastectomy.